Cellular Plasticity of Nervous System of Helminthes at the Ultrastructural Level - A.I. Golubev; L.V. Malutina; M.M. Salnikova; Ya.I. Zabotin (Учёные записки Казанского университета: Серия Естественные науки)
Radical restructuring of the organism caused by the endoparasitic way of life largely influences the organization of the nervous system as the main mediator in relations with the environment, in particular with the internal environment of the host. Based on the original data on the fine structure of the nervous system of 18 species of helminthes from the phyla Plathelminthes, Nematoda, Acanthocephala, and Annelida, the idea of some plastic possibilities of nerve and neuroglial cells of worms, which, in our opinion, reflect their parasitic way of life, has been formulated. Particular attention has been paid to the structural plasticity of neurons of free-living and endoparasitic ecomorphs of the same species of oligochaetes, the ultrastructural differences of scolex and proglottid nerve cells of cestodes in the light of the strobilar theory, and the evolutionary role of the number of hosts in the life cycle of helminthes in the formation of the ultrastructure of their neurons.